Objective and subjective evaluation of environmental noise in the Polytechnic Center Campus - UFPR - Schittini, Gabrielle Kaminski; Ribeiro Junior, Paulo Justiniano; Zannin, Paulo Henrique Trombetta (National Journal of City Management, 2021)
Noise pollution affects quality of life, well-being, and is a public health problem. In educational environments, high noise levels affect the concentration and performance of students. The Polytechnic Center Campus of UFPR is affected by several sound sources and frequented by a large number of users, which points to the need for noise management. Faced with this problem, the present study objectively and subjectively evaluates the noise in the campus. The methodology consisted of measurements that followed the standards of NBR 10151/2019 at 20 points in the region; the elaboration of maps from the insertion of parameters of relief, traffic, and characteristics of buildings and roads, calibrated according to the data collected in the measurements; and questionnaires about noise nuisance in the campus, answered by 400 users of the site. Measurement results show that the limits established at national and municipal level were not respected in a large part of the area under study. Sound maps show the surroundings of the campus delimited by dark colors that indicate high levels of noise, and internal areas demarcated by colors that represent sound pressure levels above the allowed. Interviews indicate that 60% of respondents feel annoyed by noise in the campus, and 40% consider the level of environmental noise to be reasonable. The conclusion regarding noise pollution and the influence on performance points to the need for noise control measures in the area.